CompTIA Network+ N10-008 certification guide : the ultimate guide to passing the N10-008 exam - Singh, Glen D. (Packt Publishing Ltd., 2022)
This book helps you to easily understand core networking concepts without the need of prior industry experience or knowledge within this fi eld of study. This updated second edition of the CompTIA Network+ N10-008 Certification Guide begins by introducing you to the core fundamentals of networking technologies and concepts, before progressing to intermediate and advanced topics using a student-centric approach. You'll explore best practices for designing and implementing a resilient and scalable network infrastructure to support modern applications and services. Additionally, you'll learn network security concepts and technologies to effectively secure organizations from cyber attacks and threats. The book also shows you how to efficiently discover and resolve networking issues using common troubleshooting techniques. By the end of this book, you'll have gained sufficient knowledge to efficiently design, implement, and maintain a network infrastructure as a successful network professional within the industry. You'll also have gained knowledge of all the official CompTIA Network+ N10-008 exam objectives, networking technologies, and how to apply your skills in the real world.